A Geography of the Screen: Mapmaking as Bridge between Film and Curatorial Production Processes - Ben Evans James (Arts, 2023)
Both mapping and artist documentary filmmaking offer us subjective translations of reality and strategies to relate to and represent space, sharing analogous methods of production that allow for a useful application of the spatial language of mapmaking to filmmaking. Immersing the film process within the language of mapmaking can then act as a bridge into the spatial practices of the gallery environment, curatorial practice, and exhibition design. This process is defined here as “film-mapping” and is investigated through the development of the work For the Record by Phanuel Antwi and Rhea Storr commissioned by the transmediale festival in Berlin (2021), for which the author of the present paper is the film curator. A process for film-mapping is laid out according to three stages: (1) Compose the Territory, (2) Define the Legend, and (3) Set the Modality. Understanding the production of For the Record through this mapping terminology enriches the spatial understanding of the work, providing a translation device between filmmaking and curatorial practice and mediating between the disciplines by providing a shared language.